The perception of Workplace Bullying and its relationship with Organizational Commitment among Nursing Staff at Saudia Arabia - Abdulrhman Abdullah alfawzan; Aisha Ahmad Mojamammi; Hala Mohammed Alqmash; Mohammed Rashed A Alosailan; Bandar Mohammed Siwari Alotaibi; Amro Abdulrahim Bukhari; Hela Zafer Alqahteni; Adel Dakhailallah B Alotaibi; Mohammed Abdullah alfawzan; Afeefa Mohammed Hassan Aldakheel (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Workplace bullying (WPB) represents the new truth of today’s workforce. It has sever negative effect on work environments on nurses, especially if there is a relationship for these nurseswith their organizational commitment and their intention tostay in the organization. Aim of this study to assess the prevalence of Workplace bulling among nursing staff and its relation to their organizational commitment in healthcare settings. Method: cross sectional research design was conducting using Negative act questionnaire to assess the prevalence of workplace bulling among nursing staff, and organizational commitment questionnaire , to assess the nursescommitment toward their healthcare organization, that were giving to all nurses staff who were working at governmental healthcare setting at Ghornatah Healthcare Center Al-Aqrabiyah Healthcare Center Sarrar Healthcare Center, Al-Dakhl Al-Mahdood Healthcare Center Results: the majority of nursing staff perceived moderate level of WPB. Moreover, there were statistical negative significant relationship between workplace bulling and affective commitment among studied nurses. Conclusion: Practical implicationsThe findings highlight the need for anti-bullying policies in primary healthcare.Neither satisfaction with supervisor nor satisfaction with co-workers nullifies the negative effects ofbullying on the target’s affective commitment. Preventing bullying is therefore fundamental tosustaining affective commitment.